Fictional metaphysics of fiction: Metaphysics and imagination in the humanities - Meylahn, Johann-Albrecht (HTS teologiese studies, 2017)
A very simplified description of physics could be, according to Wikipedia, natural science that involves the study of matter and its motion and behaviour through space and time. In relation to this simplified description of physics, metaphysics would then be that which gives matter, or metaphysics would be the reflection on the space and time in which matter is given. Yet, how are space and time connected? It is in language, or more specifically narrative (fiction), that space and time are connected or brought together – language, as the time-space-play in which matter and its motion and behaviour is revealed or created. One could argue that what I have just written is then also a narrative in which physics and metaphysics are given in a specific space and time, the space and time of this article. Thus, one could argue that metaphysics is fiction, but that argument itself would be fiction, and therefore one would be left with a fictional metaphysics of fiction.